Sss1p is required to complete protein translocon activation - Wilkinson, B.; Brownsword, J.; Mousley, Carl; Stirling, C. (The American Society for Biochemistry and Molecular Biology Inc, 2010)
Protein translocation across the endoplasmic reticulummembrane occurs at the Sec61 translocon. This has two essential subunits, the channel-forming multispanning membrane protein Sec61p/Sec61a and the tail-anchored Sss1p/Sec61?, which has been proposed to "clamp" the channel. We have analyzed the function of Sss1p using a series of domain mutants and found that both the cytosolic and transmembrane clamp domains of Sss1p are essential for protein translocation. Our data reveal that the cytosolic domain is required for Sec61p interaction but that the transmembrane clamp domain is required to complete activation of the translocon after precursor targeting to Sec61p. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.